Laryngeal Neuroendocrine Tumor With Elevated Serum Calcitonin: A Diagnostic and Therapeutic Challenge. Case Report and Review of Literature - Feola, Tiziana; Puliani, Giulia; Sesti, Franz; Modica, Roberta; Biffoni, Marco; Di Gioia, Cira; Carletti, Raffaella; Anastasi, Emanuela; Di Vito, Valentina; Centello, Roberta; Lenzi, Andrea; Isidori, Andrea M.; et al. (Frontiers in Endocrinology, 2020)
Introduction: Laryngeal neuroendocrine neoplasms (NENs) are rare group of NENs of the neck, that commonly show immunostaining for calcitonin (CT). Laryngeal NENs with CT hypersecretion and lymph node metastases should be included in the differential diagnosis of medullary thyroid carcinoma (MTC), becoming a diagnostic and therapeutic challenge. We report a complex case of laryngeal NEN with CT hypersecretion and a review of the literature. Case presentation: The patient was a smoker man of 59 years old that presented dysphagia, dyspnea and lateral cervical mass. At first imaging a laryngeal lesion with laterocervical lymphadenopathies was found and it resulted as a moderately differentiated neuroendocrine tumor (G2), Ki67=5%, positive for CT. Increased levels of serum CT (50 pg/ml) were found. The patient started somatostatin analogues for lesions positivity to somatostatin receptor-based imaging. After 5 months the disease progressed at 18-FDG PET-CT and also new painful cutaneous lesions occurred. Considering high serum levels of CT, differential diagnosis with MCT was required. Patient performed a thyroid echocolordoppler ultrasound, nodule fine needle aspiration, CT dosage in fine needle washout and a dynamic calcium gluconate stimulation test. After multidisciplinary evaluation it was decided to perform a total thyroidectomy associated with laterocervical lymphectomy and resection of skin metastases. No MCT was found. Two of the five resected lymph nodes, left upper parathyroid and skin lesions were metastases of NEN G2 CT positive. Two months after the surgery new painful skin lesions occurred. It was started a target therapy with everolimus 10 mg/day. After 6 months of therapy, partial metabolic response with a reduction of 53.7% of radiotracer uptake at primary tumor was detected with an improvement of patient’s quality of life. Conclusions: The present is the seventh case described in literature of laryngeal NEN associated with elevated serum CT levels and the first case with parathyroid metastasis, suggesting the importance of a correct differential diagnosis between MTC and CT-secreting laryngeal NEN, using an integrated basal and dynamic test and multimodal imaging. This is also the first time that somatostatin analogues and then everolimus were used in this setting, resulting in clinical and partial metabolic response.